A tailored TiO2 electron selective layer for high-performance flexible perovskite solar cells via low temperature UV process. (October 2016) - Jeong, Inyoung; Jung, Heesuk; Park, Minwoo; Park, Joon Suh; Son, Hae Jung; Joo, Jin; Lee, Jinwoo; Ko, Min Jae
Abstract: To realize high-performance flexible perovskite solar cells (PSCs), electron selective layers (ESL) that can be processed at low temperatures are required. Here, we develop UV-assisted solution process to prepare highly compact Nb-doped TiO2 (UV-Nb:TiO2 ) ESLs at low temperature (<50 °C). Highly crystalline TiO2 nanocrystals (NCs) stabilized with oleic acid are synthesized and the highly dispersed TiO2 NCs solution is spin-coated, followed by UV treatment. The UV exposure induces photocatalytic removal of the organic ligands and spontaneous coalescence of the TiO2 NCs, resulting in highly uniform and compact TiO2 thin films. The UV-processed TiO2 layer (UV-TiO2 ) shows higher transmittance and a better blocking effect, compared to a conventional TiO2 layer (HT-TiO2 ) prepared by high temperature sintering process. Furthermore, Nb doping of the TiO2 NCs improves the electrical conductivity and gives rise to a downward shift of the conduction band, enhancing the charge extraction. Thanks to the advantages, PSCs based on UV-Nb:TiO2 ESLs show improved photovoltaic performances and less hysteresis, compared to the HT-TiO2 ESL. The best-performing PSCs based on UV-Nb:TiO2 ESL exhibit outstanding power conversion efficiencies of 19.57% and 16.01% for rigid and flexible substrates, respectively. Graphical abstract: Highlights: Low-temperature solution processed TiO2 ESL is developed for high-performance PSCs. Nb doping of TiO2 ESL improves photovoltaic performances of PSCs. Champion cells exhibit PCE of 19.57% for rigid and 16.01% for flexible substrates.